Is Parkinson's Kinetigraph useful in frail patients with Parkinson's disease?. Issue 2 (14th May 2021) - Evans, Lauren; Mohamed, Biju; Thomas, Chris
Abstract : The use of accelerometer device technology in Parkinson's disease allows a period of continuous monitoring giving insight into disease pattern and aiding the optimisation of medication regimens. This service evaluation explores the use of such technology in a geriatrician‐led movement disorder clinic. The authors describe successful use of the Parkinson's Kinetigraph (PKG) in frail older people and discuss how frailty may have implications on the interpretation of the PKG results.